PERLINDUNGAN HUKUM PENGGUNA MARKETPLACE TERHADAP DUGAAN PELANGGARAN HAK PRIBADI YANG DILAKUKAN JASA PENGIRIMAN BERDASARKAN HUKUM POSITIF DI INDONESIA (Contoh Kasus Viral Transaksi Jual Beli “Cash On Delivery”) - Jesselyn Valerie Herman; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
Trading through the market has increased along with the times, especially during the COVID19 pandemic. The number of parties involved is due to the legal consequences of its own in its implementation in the field, especially shipping service companies that play an important role in the implementation of distributing goods to buyers. However, in practice, there are often complex problems between the courier and the buyer who are the end of online buying and selling transactions. In this study, two problems will be discussed, i.e. how is legal protection and who can be responsible for the alleged violation? considering that the delivery service is only for delivering goods and taking payments using the Cash On Delivery (COD) method. This study used normative legal research methods, secondary data types derived from library materials with qualitative descriptive data collection, followed by a statute approach and a case approach. Based on the results of the study, it shows that the innovations caused by the COD payment mechanism do not yet have protection for buyers and couriers because there are no guidelines that provide clear guidelines, especially in the procedures and limitations of taking photos as electronic evidence, resulting in not being able to overcome the problems faced by couriers in sending goods. with the COD system. Therefore, the government has an important role in supervising the rules issued unilaterally by electronic system operators in carrying out transactions through applications regulated in positive law in Indonesia. If there is a violation of the provisions of electronic evidence such as the distribution of expedition videos without the buyer's consent, then both the government and the organizers can give a warning and a strong legal basis so that the buyer can fight for his rights against the actions of the expedition courier as a delivery person.